Mechanisms and clinical significance of Tumarkin-like phenomenon during the final step of the Epley and Semont maneuver: insights from virtual simulation and literature review - Yang, Ruihu; Yang, Xiaokai (Frontiers in Neurology, 2025)
ObjectivesThis study aims to investigate the mechanisms underlying the Tumarkin-like phenomenon during the final step of the Epley and Semont maneuvers for benign paroxysmal positional vertigo (BPPV) through virtual simulation and a comprehensive literature review. We also provide clinical recommendations to improve treatment outcomes and optimize repositioning protocols.MethodsA three-dimensional virtual simulation model was developed to accurately represent the semicircular canals, otoliths, and associated vestibular structures. Key parameters governing otolith movement were defined based on physiological data. Virtual experiments were conducted to simulate the final steps of the Epley and Semont maneuvers, allowing detailed observation of otolith movement. The study followed ethical guidelines throughout.ResultsVirtual simulations revealed distinct otolith movement patterns during the Epley and Semont maneuvers. In the standard Epley maneuver, otoliths should enter the utricle before the final sitting up step, resulting in no further movement or symptoms. Conversely, in the Semont maneuver, otoliths may enter the utricle through the common crus when sitting up, potentially causing vertigo, nystagmus, and unsteadiness. Improper execution of either maneuver can lead to unexpected otolith movements and symptoms. The clinical significance of symptoms during the final step varies between the two maneuvers and is closely linked to proper execution. The study also highlights the importance of head positioning during the maneuvers, with specific angles influencing otolith movement and symptom manifestation.ConclusionsThe findings provide a detailed understanding of otolith movement dynamics during the final steps of the Epley and Semont maneuvers. The results challenge existing views on the correlation between dizziness and successful repositioning, emphasizing the need for personalized treatment approaches and accurate maneuver execution. This study contributes to refining repositioning protocols, optimizing outcomes, and advancing our comprehension of BPPV dynamics. Future clinical studies are needed to verify these simulation results and develop more precise and personalized BPPV diagnosis and treatment methods.